Transformative Learning Theory in Higher Education: Perspective Transformation for Students of a Department of Education in Greece (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
The following article explores the perspective transformation in Greek higher education using the Learning Activities Survey (LAS) questionnaire and semi-structured interviews. More specifically, the research occurred in the Department of Educational Sciences and Early Childhood Education at the University of Patras, Greece. The results have shown that 93.3% of the students have gone through two to five phases with the disorienting dilemma phase concentrating the highest percentage (58.7%). The students experienced changes regarding their way of thinking and behavior, changes in the perceptions as regards their profession and in some cases changes in their beliefs or expectations.